Severe Hypertriglyceridemia Presenting as Superior Sagittal Sinus Thrombosis - Sanyal, Debmalya; Chaudhuri, Soumyabrata Roy; Majumder, Anirban (Journal of the ASEAN Federation of Endocrine Societies, 2014)
We report a case of a 38-year-old Indian male who presented with severe throbbing headache spreading diffusely from occipital to nuchal regions. He was detected to have superior cerebral (sagittal) venous sinus thrombosis (CVST) with severe hypertriglyceridemia without any coagulation abnormalities or autoimmune disease. Our case highlights the need for clinicians to consider CVST among patients with uncontrolled hypertriglyceridemia. New prognostic measures may become necessary having an implication on the risk of recurrence and duration of anticoagulant therapy in CVST.